2019
DOI: 10.1371/journal.pone.0217693
|View full text |Cite
|
Sign up to set email alerts
|

“I would love if there was a young woman to encourage us, to ease our anxiety which we would have if we were alone”: Adapting the Mothers2Mothers Mentor Mother Model for adolescent mothers living with HIV in Malawi

Abstract: Background Pregnant and post-partum adolescent girls and young women (AGYW) living with HIV in sub-Saharan Africa experience inferior outcomes along the prevention of mother-to-child transmission of HIV (PMTCT) cascade compared to their adult counterparts. Yet, despite this inequality in outcomes, scarce data from the region describe AGYW perspectives to inform adolescent-sensitive PMTCT programming. In this paper, we report findings from formative implementation research examining barriers to, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 34 publications
3
54
0
1
Order By: Relevance
“…Safety and violence exposure A lack of social and psychosocial support has been reported as a barrier for engagement with PMTCT and maternal and child health services (Carbone et al, 2019;Kumar et al, 2018), highlighting how social support intersects with multiple domains for adolescent mothers. Pregnant and parenting adolescents are at a greater risk of intimate partner violence (IPV) compared to their nonpregnant, non-parenting peers (Closson et al, 2019).…”
Section: Health and Well-being Of Adolescent Mothers Affected By Hiv mentioning
confidence: 99%
See 2 more Smart Citations
“…Safety and violence exposure A lack of social and psychosocial support has been reported as a barrier for engagement with PMTCT and maternal and child health services (Carbone et al, 2019;Kumar et al, 2018), highlighting how social support intersects with multiple domains for adolescent mothers. Pregnant and parenting adolescents are at a greater risk of intimate partner violence (IPV) compared to their nonpregnant, non-parenting peers (Closson et al, 2019).…”
Section: Health and Well-being Of Adolescent Mothers Affected By Hiv mentioning
confidence: 99%
“…Uptake and repeat pregnancy prevention interventions have tried to replace the success of adult adherence clubs and peer support groups, but with limited success (Kossow et al, 2012;Orne-Gliemann et al, 2017). Emerging qualitative evidence on programming designed specifically for adolescent mothers is promising, although quantitative evidence is not yet available for these initiatives (Carbone et al, 2019;Kossow et al, 2012).…”
Section: Programmes Reaching Adolescent Mothers Affected By Hiv and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that peer‐centred approaches can effectively be combined with other interventions [72] and encourage other reproductive health behaviours [73]. These trial findings are largely supported by qualitative research, which confirm the overall feasibility and acceptability of the intervention [74‐76], including among adolescents [77]. For widespread implementation, however, adaptations may be required to fully optimize the role of peer supporters within the health system [78].…”
Section: Resultsmentioning
confidence: 73%
“…Income generation was the most stated topic and was related to participants' inability to continue their education and thus nd employment to support themselves and their families. Similarly, Carbone and colleagues (2019) used FGDs with adolescent mothers aged 15-19 in Malawi to inform the development of a program to educate on the prevention of mother-to-child transmission of HIV (39). Adolescent mothers in their study requested education on subjects not directly related to transmission, such as poverty, food insecurity, economic disempowerment and nancial dependence, which were often cited as barriers to care.…”
Section: Discussionmentioning
confidence: 99%